2011
DOI: 10.1007/s00586-011-1930-3
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal balance disorders in severe degenerative spine. Can we identify the compensatory mechanisms?

Abstract: Introduction Aging of the spine is characterized by facet joints arthritis, degenerative disc disease and atrophy of extensor muscles resulting in a progressive kyphosis. Recent studies confirmed that patients with lumbar degenerative disease were characterized by an anterior sagittal imbalance, a loss of lumbar lordosis and an increase of pelvis tilt. The aim of this paper was thus to describe the different compensatory mechanisms which are observed in the spine, pelvis and/or lower limbs areas for patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
240
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(262 citation statements)
references
References 23 publications
(30 reference statements)
11
240
0
11
Order By: Relevance
“…Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing. Decreasing values in lumbar lordosis and sacral slope angles in patients with DDD are consistent with the spine literature, where these sagittal parameters are used to evaluate individual sagittal balance [4,5,28]. Interestingly, similar to a previous study evaluating sagittal balance during standing in patients undergoing THA [24], some patients with DDD in our study had such excessive posterior pelvic tilt and lack of lumbar lordosis that they required knee flexion to adapt, because hip extension was insufficient.…”
Section: Discussionsupporting
confidence: 89%
“…Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing. Decreasing values in lumbar lordosis and sacral slope angles in patients with DDD are consistent with the spine literature, where these sagittal parameters are used to evaluate individual sagittal balance [4,5,28]. Interestingly, similar to a previous study evaluating sagittal balance during standing in patients undergoing THA [24], some patients with DDD in our study had such excessive posterior pelvic tilt and lack of lumbar lordosis that they required knee flexion to adapt, because hip extension was insufficient.…”
Section: Discussionsupporting
confidence: 89%
“…Frequently, this mechanism uses muscle force to improve alignment, with a resulting spinal shape that restores the gravity line position and horizontal gaze [22][23][24]. In this stage, the individual is able to meet these alignment goals, but at the price of increased muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…The LL will structurally reduce as a result of segmental discopathy and loss of disc height [13,25]. Subsequently, the loss of lordosis potentially leads to the anterior translation of the gravity axis (increasing SVA).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the loss of lordosis potentially leads to the anterior translation of the gravity axis (increasing SVA). In compensation, pelvic backtilt (PT increasing and SS decreasing and SFD increasing), which is secondary to the action of the hip extensor muscles acts to limit the forward movement of the gravity axis in these patients [2,13,15,16,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation